A giant keratoacanthoma of the cheek - Pica Alfieri, Edoardo; Sisti, Andrea; Nisi, Giuseppe; Brandi, Cesare; Grimaldi, Luca; D'Aniello, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Keratoacanthoma (KA) is a cutaneous tumor arising on sun-exposed skin and characterized by self-limiting growth and involution. We reported a case of a 92-year-old man presented a 4.5x3.5 cm nodular lesion with a central keratin-filled crater on his left cheek. We performed surgical excision and histopathological examination revealed a keratoacanthoma with perineural invasion. A close follow-up was carried out. (www.actabiomedica.it)